Analysis of the Formal and Non-Formal Madrasah Accreditation System Under the Ministry of Religious Affairs and Its Implications for the Learning System - andraini, Beta; Sari Wulandari; Desy Eka Citra Dewi (International journal of technology and education research, 2026)
The madrasah accreditation system administered by the Ministry of Religious Affairs of theRepublic of Indonesia (Kemenag) is a strategic instrument for measuring and improving the quality ofIslamic education, both in formal and non-formal pathways. This article examines in depth howaccreditation mechanisms are applied to both pathways, traces their impact on teaching practices inthe field, and identifies various structural barriers that impede their effectiveness. Using asystematic literature review approach, this study analyzes official regulations, quality assuranceagency reports, and empirical research published between 2020 and 2024. Findings reveal that whilethe formal accreditation framework is relatively structured and consistent, its implementation stillfaces significant institutional capacity gaps, particularly in madrasahs located in remote areas andnon-formal pesantren that frequently operate with severely limited resources. Furthermore, thestudy finds that accreditation's influence on learning quality tends to be indirect and contingent onschool leadership commitment and teacher quality. The implications of these findings include theneed for reform of assessment instruments that are more responsive to local contexts,strengthening of human resource capacity, and the development of a sustainable post-accreditationmonitoring system. This article aims to contribute to the development of a more inclusive andevidence-based Islamic education policy.Keywords: madrasah accreditation, Ministry of Religious Affairs, non-formal education, learningquality, quality assurance